Determinant Analysis of Public Participation in the Implementation of Greening in Kampung Iklim 2 Ilir, Palembang - Herdani, Yaumilia Ismiranti Putri; Dahlan, Zulkifli; Susanti, Rahmi (Indonesian Journal of Environmental Management and Sustainability, 2020)
Implementation of greening has a positive impact on anticipating and minimizing the impact of climate change. This study aims to analyze community participation in the implementation of greening that has been carried out in ProKlim 2 Ilir, Palembang. The population of this study was 639 households and there were 90 households as respondents. This research uses quantitative methods with a cross-sectional design. Data collection instruments are questionnaires, observations, interviews, and documentation. Data were analyzed using multiple logistic regression. The results showed participation of the community (54.4%) in the implementation of greening was classified as still bad. Characteristics of the community are mostly aged middle adults (47.8%), mostly female (72,2%), highly educated (>SMA) of 88.9%, medium knowledge (51.1%), including a length of stay in the old enough category (72.2%), and has the highest employment as a housewife (41.1%). The result of multiple logistic regression showed a variable that the education level variable (OR=5.174) influence the participation of the community in the implementation of greening.